PENDAMPINGAN GURU DALAM PENGEMBANGAN EKOSISTEM KAYA TEKS UNTUK LITERASI DAN NUMERASI SEKOLAH - Barokah, Awalina; Ira Restu Kurnia; Bramianto Setiawan; Zakiyah Ismuwardani; Winda Oktavia Amri (STKIP Subang, 2026)
The low level of literacy and numeracy skills among primary school students remains a major challenge in improving educational quality. One strategic effort to address this issue is through the development of a text-rich ecosystem integrated into classroom learning. This community service program aimed to enhance teachers’ competencies in designing and implementing a text-rich ecosystem to support students’ literacy and numeracy skills. The program employed a participatory and collaborative approach through training, workshops, mentoring, implementation, and evaluation stages. The participants consisted of 17 primary school teachers selected using purposive sampling. Data were collected through observations, interviews, questionnaires, and documentation, and were analyzed descriptively. The results showed a significant improvement in teachers’ understanding, indicated by an increase in the average pre-test score from 62.1 to 86.3 in the post-test, with an N-Gain score of 0.64 categorized as moderate. In addition, teachers were able to develop and implement text-rich environments in classrooms, such as reading corners, numeracy posters, and text-based learning media, which positively impacted students’ engagement and participation in learning. Therefore, mentoring teachers in developing a text-rich ecosystem is proven to be effective in improving teacher competence and supporting more meaningful literacy and numeracy learning.